Ultrafine Bi2WO6 nanoparticles prepared by flame spray pyrolysis for selective acetone gas-sensing - Matawee Punginsang (2018)
© 2018 Elsevier Ltd In this work, ultrafine layered-perovskite oxides nanoparticles of Bi2WO6 were synthesized by a single-nozzle flame-spray pyrolysis (FSP) method with the bismuth (III) nitrate pentahydrate and tungsten (VI) ethoxide (2:1 mol) precursor solution for the first time. Structural characterizations by electron microscopy and X-ray analysis demonstrated the formation of spherical Bi2WO6 nanoparticles (3–30 nm in diameter) with an orthorhombic phase, very high phase purity, very high specific surface area (~ 197.8 m2/g), and high thermal stability. The achieved specific surface area is much larger than those synthesized by other synthesis and aerosol processing techniques. The optical band gap of Bi2WO6 nanoparticles was found to be ~ 2.7 eV by UV–vis diffuse reflectance spectroscopy. In addition, Bi2WO6 nanoparticles exhibited photoluminescence peaks at 424, 485 and 529 nm. The detailed analysis of experimental data and FSP process suggested that the single-phase Bi2WO6 nanoparticles were formed via the gas-phase reaction between Bi2O3 and WO3. From gas-sensing measurements, the flame-made Bi2WO6 nanoparticles displayed a good response of 3.72–2000 ppm acetone at 350 °C and good selectivity against C6H6, C8H10, C2H5OH, CH2O, C7H8, NO, NO2, H2S, H2 and CH4. Therefore, the flame-made Bi2WO6 nanoparticles can be a promising alternative as a base material for gas-sensing applications.